Nordic Memories of the East. Tetsuro Yoshida and the myth of traditional Japanese house in Erik Gunnar Asplund, Aino Aalto and Alvar Aalto - Iván Rincón-Borrego; Ramón Rodríguez-Llera (VLC Arquitectura)
Traditional Japanese architecture played an important role in the development of modern European architecture, especially from the beginning of the 20th century. Based on this extensively documented thesis, the influence of Japanese culture and the traditional Japanese house on the figures of Erik Gunnar Asplund, Aino Aalto and Alvar Aalto, especially during the 1930s, is analysed. The study describes how these authors found inspiration in the East, as well as their contacts and sources of reference. Finally, it explains the extent to which they reinterpreted Japanese aesthetics in their designs, especially analysing the case of the Villa Mairea winter garden. In this context, the research points to the decisive role played by the figure of Tetsuro Yoshida and his text Das japanische Wohnhaus (1935) for the interests and designs of these Nordic authors.